ANTIOKSIDAN BIJI KAKAO: PENGARUH FERMENTASI DAN PENYANGRAIAN TERHADAP PERUBAHANNYA (ULASAN) - Ratri Retno Utami (Jurnal Industri Hasil Perkebunan, 2018)
The main cocoa antioxidant compounds are flavanols that consist of monomer (epicatechin and catechin) and oligomers from dimers to decamers (procyanidin), with small quantity of anthocyanin (cyaniding glucoside) and flavonol (quercetin glycoside). Cocoa processing stages that affect antioxidant compounds changes atre fermentation and roasting. Fermentation causes decrease of polyphenol content due to polyphenols diffusion out of the cotyledons, furthermore polyphenols undergo oxidation and condensation. Roasting temperature more than 70oC cause loss of (+)-catechin. During roasting, protein that bounded to the cell wall (cellulose and pectin) undergo Maillard reaction where its products potentially as antioxidants. This study is useful to know the proper of cocoa beans processing so antioxidant content can be maximized.